Dakwah Multikultural Sebagai Strategi Pencegahan Radikalisme - Syahruddin (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
This study explores multicultural da’wah strategies in the digital era, emphasizing the importance of a dialogical, inclusive, and context-sensitive approach. In Indonesia’s pluralistic society, da’wah functions not only as a means of religious dissemination but also as a social instrument to strengthen the values of tolerance, justice, and humanity. Using a descriptive qualitative approach, this research examines relevant literature on the role of educational institutions, the challenges of digital da’wah, and the involvement of civil society in developing multicultural Islamic communication. The findings reveal that effective multicultural da’wah requires preachers to understand social and cultural diversity so that Islamic messages can be delivered peacefully and constructively. Moreover, digital media plays a vital role in broadening da’wah outreach by promoting messages of moderation and peace. Educational institutions and community organizations contribute significantly by instilling multicultural values through education and religious programs. Thus, multicultural da’wah in the digital age can serve as an effective medium to foster social harmony and reinforce an inclusive Islamic identity that embraces diversity. Penelitian ini membahas strategi dakwah multikultural di era digital dengan menekankan pentingnya pendekatan dakwah yang dialogis, inklusif, dan kontekstual. Dalam masyarakat Indonesia yang majemuk, dakwah tidak hanya berfungsi sebagai sarana penyebaran ajaran agama, tetapi juga sebagai instrumen sosial untuk memperkuat nilai-nilai toleransi, keadilan, dan kemanusiaan. Melalui pendekatan kualitatif deskriptif, penelitian ini mengkaji berbagai literatur yang relevan tentang peran lembaga pendidikan, tantangan dakwah digital, serta keterlibatan masyarakat sipil dalam mengembangkan dakwah multikultural. Hasil kajian menunjukkan bahwa dakwah multikultural menuntut kemampuan da’i memahami keragaman sosial dan budaya masyarakat agar pesan Islam dapat diterima secara damai dan konstruktif. Selain itu, media digital berperan penting dalam memperluas jangkauan dakwah melalui penyebaran pesan-pesan moderasi dan perdamaian. Lembaga pendidikan dan komunitas masyarakat memiliki kontribusi signifikan dalam menanamkan nilai-nilai multikultural melalui pendidikan dan program keagamaan. Dengan demikian, dakwah multikultural di era digital dapat menjadi sarana efektif untuk membangun harmoni sosial dan memperkuat identitas keislaman yang terbuka terhadap perbedaan.